EMPLOYEE NET PROMOTER SCORE: A DEEP DIVE INTO A SINGLE QUESTION. - Meier, Emily M (East Carolina University)
The primary goal of the study was to assess Employee Net Promoter Score from a qualitative lens. This study also aimed to assess Employee Net Promoter Score's relationship to other work and personality variables, namely burnout, engagement, turnover intentions, and proactive personality. Quantitative results show a strong relationship between turnover intentions and Employee Net Promoter Score, with turnover intentions not only correlating, but predicting Employee Net Promoter Score in all samples tested. Engagement and burnout were consistent predictors, but proactive personality was not. Qualitative analysis uncovered many themes related to Employee Net Promoter Score, including benefits, people, organization, and change management. Scoring Employee Net Promoter score also came into question, with further research needed to better understand the implications of cutting promoters at a score of 9.
Keywords: Employee Net Promoter Score; Turnover Intentions; Proactive Personality; Employee Engagement; Employees--Attitudes; Burn out (Psychology); Industrial hygiene; Labor turnover